The relationship between frailty syndrome and self-care ability in the elderly with heart failure - Leila Zahed Nakhjiri; Azar Darvishpour; Parand Pourghane; Bahareh Gholami Chaboki (Journal of Education and Health Promotion, 2021)
BACKGROUND: Identification of frailty syndrome in patients with heart failure can affect the process of the disease and their ability to self-care. Considering the lack of a study on the relationship between frailty syndrome and self-care ability in the elderly with heart failure in the Guilan province, the North of Iran, this study was conducted to determine the relationship between fertility syndrome and self-care ability in these patients. MATERIALS AND METHODS: The present cross-sectional correlational study was conducted in 2020. Research settings were the CCU and post CCU wards in the East Guilan public hospitals. The sample size was 125 people who were selected by the convenience sampling method. The research tools include; Self-Care Heart Failure Index and Tilburg Frailty Index Questionnaires. Data were analyzed using SPSS software version 20 using descriptive and inferential statistics with a significance level of 0.05. RESULTS: The results showed that the mean score of frailty syndrome in the elderly with heart failure was 5.44 ± 2.47. In addition, the mean score of self-care in the elderly with heart failure was 67.16 ± 10.96. There was a significant and negative correlation between frailty syndrome and the ability to care in the elderly with heart failure (P < 0.001, r = −0.358). CONCLUSIONS: According to the results, the elderly with fragility syndrome cannot take good care of themselves. This indicates that in the management of heart failure, the assessment of frailty syndrome as a care/treatment goal in the care programs of these patients should be considered.